KEBUTUHAN EKONOMI DAN KAITANNYA DENGAN PERCERAIAN (STUDI ATAS CERAI GUGAT DI PENGADILAN AGAMA AMBON) - Husin Anang Kabalmay (IAIN Ambon, 2017)
One major problem often encountered husband and wife, is the economic needs of the household. The husband's inability meet the needs of the economy will lead to marital disharmony easily trigger a divorce. So the data in the Religious Ambon showed that the biggest factors causing disharmony divorce is closely related also to the economic problems. In that regard the divorce rate in the Religious Ambon predominantly ethnic immigrants from outside the Moluccas. While the divorce rate is relatively low indigenous population, which caused still strengthening kinship, kinship solidarity and local wisdom. In addition, my wife looked at divorce divorce for reasons of economic pressures, as an irresponsible husband, greeting quantity divorce from husband would hamper meet daily needs; and lazy husband who works a dishonorable act. Keywords: economic needs, contested divorce